Analisa Pengaruh Perubahan Tata Guna Lahan Terhadap Saluran Drainase Kecamatan Rumbai Pesisir Kota Pekanbaru Menggunakan Program Bantu EPA SWMM 5.0 (Studi Kasus : Kawasan Jalan Yos Sudarso) - Ferdi Wranda; Imam Suprayogi; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The flood problem and inundation local often occuring in regions Rumbai Pesisir, precisely in the intersection of Yos Sudarso Street. The main cause of the flood and water was changes to land of the natural environment to development , raising the surface watertight , for example the way , commercial area , the sidewalk , and residential . This change reduce , disturbing vegetation natural or eliminate the ground up , the natural and drainage patterns that prevents , vaporize , store , issued slowly and meresapkan water . The impact of changes to land management in the region yos sudarso was the increasing flow of direct surface (run off) and parse water to seep in ground which can make puddles .On pesing , analysis was conducted hydrology with the data of rain in 20 years from station office hydrology. Analysis hydrology planning it uses distribution probability logs pearson type 3 and with on the EPA SWMM with a period of flood re until 2033. Obtained discharge minimum flood of 46,648 m3/seconds and discharge flood maximum of 251,252 m3/seconds. On planning dimensions drainage channel namely worn varying dimensions existing 2m x 1.6m and dimensions plan 2.5m x 2.5m. in the calculation of using program channel EPA SWMM planned in road area yos sudarso with dimensions 2m x 1.6m currently unable to accommodate water during the incident the period flood repeated 2033. Furthermore planning a drainage channel dimension Street Area Yos Sudarso changed to 2.5 m x 2.5 m able to accommodate water when genesis flood plan and land use change the period until the year 2033. Engineer Estimate for the development of the drainage channel Street area Yos Sudarso Rumbai Pesisir Sub-Districts requires total costs incurred is Rp 35.524.770.000,00 (Thirty five billion five hundred twenty-four million seven hundred seventy thousand rupiah).Keyword: Analysis Hydrology, Drainage Dimension, EPA SWMM, Engineer Estimate